The Effectiveness of a Counseling-Psychological Program on the Mental Health of a Sample of Obese Women (Journal of the College of Basic Education, 2025)
The research aims to:1- Develop a mental health scale for a sample of obese women.2- Identify the level of mental health for a sample of obese women.3-Develop a psychological counseling program for mental health for a sample of obese women.4-Identify the impact of the psychological counseling program on the mental health of a sample of obese women.The research hypotheses were:1-A decrease in the level of mental health for a sample of obese women.2-The psychological counseling program has a positive impact on supporting the mental health of a sample of obese women.The researcher used a descriptive approach using a survey method to develop a mental health scale. She also used an experimental approach using two equivalent groups with a pre-test and post-test design. The research community was defined as the women participating in the Health Institute with obesity, numbering (119) participants. The research sample that underwent the experiment consisted of:To achieve the objectives of the current research, a scale on mental health was developed to suit the research sample. Following scientific steps in developing the scale, after completing the scale construction and design procedures, the final version of the scale consisted of (30) items and (3) domains. A planning system was used to prepare the psychological counseling program, based on several steps.The SPSS statistical package for social sciences was used to extract the research results. After presenting, analyzing, and discussing the results, the following conclusions were reached:1- The psychological counseling program had a clear impact on developing the mental health of participants in the Health and Fitness Institute from the experimental group in the post-test.2-There were statistically significant differences between the control and experimental groups, in favor of the experimental group, regarding the mental health of women participating in the Health and Fitness Institute.